(396) In seeking by the Nonplex Method in Non-Linear Programming البحث باستخدام طريقة نونبلكس في البرمجة غير الخطية - Fricsh, R. (معهد التخطيط القومى, 2024)
The study explores the significance of the infrastructure effect (Infra-effect) in national planning and how investments influence the coefficients in a national planning model. The concept is elaborated in a memorandum dated December 13, 1963. Incorporating the infra-effect renders the mathematical programming problem nonlinear, often at least quadratic. While this does not pose major challenges as long as the admissible region is convex and the reference function is concave, ensuring convexity becomes challenging, particularly when dealing with dependent, nonlinear functions that are bounded on both sides.